Analysis of The Factors That Influence Auditor Switching in Bank Companies Listed on The Indonesian Stock Exchange in 2017-2021 - Putra, Ubaidillah Perdana; Susbiyani, Arik; Afroh, Ibna Kamelia Fiel (West Science Journal Economic and Entrepreneurship, 2024)
Auditor switching is a change of KAP or auditor made by the company for a reason or there are certain factors from the company and from the auditor itself. Auditor Switching in Indonesia is one of the regulations required by the Indonesian government as an effort to maintain auditor independence. This study aims to analyse the effect of audit opinion, institutional ownership, management change, and financial distress on auditor switching. The results of this study reveal several important findings. First, Audit Opinion has an insignificant influence on auditor switching this is because in general the sample of banking companies mostly get an unqualified opinion. Second, Institutional Ownership has an insignificant influence on auditor switching because the high proportion of institutional ownership in a banking company does not guarantee auditor switching. Third, Management Change has a significant influence on auditor switching because management wants a KAP that can meet management's needs in managing the company. Finally, Financial Distress has a significant influence on auditor switching because when a company experiences financial distress, the company will make a change of KAP. The potential bankruptcy experienced by the company causes company management to try to prevent bankruptcy which results in liquidation.